ANALISIS KUALITAS PENGELOLAAN KEUANGAN DAERAH DI PROVINSI PAPUA - Yundy Hafizrianda; Ida Ayu Purbariani; Boy Pieter Nizu Kekry (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
In general, the aim of this study is to measure and analyze the quality of regional financial management in the Papua Provincial Government in a structured and comprehensive manner. Where the measurement and analysis methods used include a model of fiscal independence, the effectiveness and efficiency of local government revenue, as well as expenditure ratio models. Based on the results of measurements with the local government budgeting management analysis tools founds that overall the quality of local government budgeting management of the Provincial Government of Papua is good. The indicators of the quality of local government budgeting management can be seen from the timeliness in preparing the APBD-Induk  and APBD-Perubahan, the efficiency and effectiveness of local government revenue, the ratio of PAD to local government revenue, absorption of Government Expenditure, the trend of SILPA, and BPK's opinion on LKPD. The quality of local government budgeting management by using the Timeliness Indicator in the preparation of the APBD-Induk and APBD-Perubahan looks varied and said to be of good quality, especially in 2015 and 2016, both the determination of APBD-Induk and APBD-Perubahan indicated on time. Furthermore, when analyzed in the trend of local government revenue, categorized quite well, where the level of efficiency and effectiveness is high, but its independence is still very low. In the composition of local government expenditure, capital expenditure tends to be always above employee expenditure, besides that the absorption capacity of local government expenditure is good because it averages close to 90% per year during the 2013-2015 period, so that the overall quality of local government budgeting management when observed from the performance of local government expenditure rated good. Next, in the SILPA APBD position, it tends to be always in a fluctuating positive value during 2013-2015, and categorized as good quality. Finally, based on the opinion of the BPK (Badan Pemeriksa Keuangan) on the LKPD (Laporan Keuangan Pemerintah Daerah), throughout 2015-2018 the Papua Province always received the title of WTP (Wajar Tanpa Pengecualian), so from the development of this opinion indicated that the local government budgeting management of the Provincial Government of Papua is very good.